2013
DOI: 10.1007/s10461-013-0578-x
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Clustering of High Risk Sexual Behaviors in “Hot-Spots” for HIV and Sexually Transmitted Infections in Kwazulu-Natal, South Africa

Abstract: We investigated geographical variations of three sexually transmitted infections (STIs) namely chlamydia, gonorrhea and syphilis in the greater Durban area, so as to optimize intervention strategies. The study population was a cohort of sexually active women who consented to be screened in one of three biomedical studies conducted in Durban. A total of nine local regions collectively formed three clusters at screening, five of which were previously defined as HIV hot-spots. STI cases were geo-coded at the cens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 20 publications
4
22
0
2
Order By: Relevance
“…In others the pattern is less clear. This work confirms the conclusions made by other studies in the region that identified heterogeneous pattern of micro–epidemics within a more generalised epidemic [1012,14,17]. Our results confirm trends shown by Tanser and colleagues [8] of considerable local geographic variation in HIV prevalence in a rural area of Kwa Zulu Natal South Africa.…”
Section: Discussionsupporting
confidence: 93%
“…In others the pattern is less clear. This work confirms the conclusions made by other studies in the region that identified heterogeneous pattern of micro–epidemics within a more generalised epidemic [1012,14,17]. Our results confirm trends shown by Tanser and colleagues [8] of considerable local geographic variation in HIV prevalence in a rural area of Kwa Zulu Natal South Africa.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study revealed that being young and unmarried are strong contributing risk factors for STI acquisition in our local population. 3,17 Upon adjusting for these contributing factors, women in inter-GAD partnerships had a 32% decreased risk of STI acquisition compared to those in intra-GAD relationships (p ¼ 0.066).…”
Section: Discussionmentioning
confidence: 99%
“…1 The high HIV incidence rate among young women is disconcerting and summons scrutiny of associated social factors. [1][2][3] One such social factor is age disparate (AD) relationships, which refers to relationships in which the age gap between sexual partners is five years or more. 4 In a recent national survey, there was a significant gender difference relating to age disparity with 34% of all female adolescents aged 15-19 years old reporting ever having had a partner more than five years older than themselves, compared to only 4% of their corresponding male peer group.…”
Section: Introductionmentioning
confidence: 99%
“…Although HIV incidence has stabilised in South Africa over the past decade, the country sustains hyper-epidemics within specific regions and populations 2 3. The National Institutes of Health proposed the ‘Seek, Test, Treat and Retain’ (STTR) strategy to curtail HIV transmission by expanding HIV testing to seek undiagnosed cases (‘Seek’ and ‘Test’), bringing patients into HIV treatment (‘Treat’), and retaining them in clinical care (‘Retain’) 4.…”
Section: Introductionmentioning
confidence: 99%